2017
DOI: 10.7861/clinmedicine.17-2-121
|View full text |Cite
|
Sign up to set email alerts
|

Current characteristics, challenges and coping strategies of young people with cystic fibrosis as they transition to adulthood

Abstract: This study provides detailed data on the current characteristics, perceptions and outcomes of 45 young people with cystic fi brosis (CF) as they transition into adulthood. Although many had severe disease, they generally coped well, found attendance at a transition clinic helpful and welcomed the increased independence of an adult healthcare environment. Levels of psychological distress were low with only 15.6% having anxiety and 6.7% depression. The main psychological coping strategy used was optimistic accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 23 publications
1
32
1
2
Order By: Relevance
“…Worse EF demonstrated moderate relations to higher treatment burden, worse lung function, and older age. These factors generally emerge together as CF advances, rendering them unavoidable and generalizable to the general population of individuals with CF 43 . This finding is aligned with previous research in CF identifying higher rates of ADHD symptomatology in adults with CF 15 …”
Section: Discussionsupporting
confidence: 85%
“…Worse EF demonstrated moderate relations to higher treatment burden, worse lung function, and older age. These factors generally emerge together as CF advances, rendering them unavoidable and generalizable to the general population of individuals with CF 43 . This finding is aligned with previous research in CF identifying higher rates of ADHD symptomatology in adults with CF 15 …”
Section: Discussionsupporting
confidence: 85%
“…A more recent study performed structured interviews with 45 recently transitioned patients, and noted that although there was significant individual variability, the mean FEV1 and BMI did not change 1 year after transfer. Importantly, there was a sense of optimistic acceptance about the future . As more centers are becoming engaged in the creation of a formalized transition program, it would behoove the community to study post‐transition outcomes further, including BMI, FEV1, pulmonary exacerbations, and patients lost to follow‐up after transfer.…”
Section: Cf Risementioning
confidence: 99%
“…In the Netherlands, around 1500 people live with cystic fibrosis (CF) and more than half are over 18 years of age . Their life expectancy has improved and is likely to improve further with the advent of CF transmembrane conductance regulator modulator therapies . CF care in the Netherlands has been concentrated in seven centers, each with an adult and a pediatric department.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no shared model, the TC's core principle is that professionals from both pediatric care (PC) and adult care (AC) deliver outpatient care in preparation for the upcoming transfer . Studies evaluating TCs in CF care have reported improved health status, self‐care and self‐advocacy skills, and more independence . However, most studies did not include a controlled pre‐post outcome evaluation, and the body of evidence for effects is still small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation